Translation Accounting and the Islamic Monetary System: A Historical Approach and Solutions to Global Inflationary Distortions - Moh Syarif Jauhari; Khusnudin (al-Afkar, Journal For Islamic Studies, 2025)
This study explores the mechanisms of translation accounting and its relevance to the principles of the Islamic monetary system in addressing global inflationary distortions. The Islamic monetary system, which is based on the intrinsic value of commodity-based currencies such as gold and silver, offers greater exchange rate stability than the conventional fiat-based monetary system. Using a descriptive qualitative approach, this study examines the role of translation accounting in converting financial statements across currencies and compares the stability between Islamic and conventional monetary systems. The analysis shows that the application of Islamic principles, including the prohibition of usury and speculation, can reduce exchange rate volatility, prevent economic distortions, and create financial statements that better reflect real values. This study concludes that the Islamic monetary system has the potential to be a sustainable alternative to address the challenges of global inflation and enhance international economic stability.